Jože Pučnik - Komel, Dean (Traditiones (Ljubljana), 2014)
For different reasons, but primarily because of the experience of a political prisoner, Jože Pučnik more or less rejected to play the role of "a political personality". Slovenian public only reluctantly places him amongst the most important political personalities of the 20th century. At the same time, however, his political activity was based precisely upon the apology of "a free personality".
Keywords: political history; Pučnik, Jože, 1932-2003; politična zgodovina; cultural anthropology; kulturna antropologija; personalities; Slovenia; znamenite osebnosti; Slovenija